(untitled) (Research, Society and Development, 2020)
Fungi-growing ants from fresh plant material (Acromyrmex and Atta) are of great economic importance, as they severely defoliate agricultural crops. Chemical control is the most used for the control of these species, causing several environmental problems. As a result, there is a concern and pressure from society for alternatives to control. Biological control programs, using entomopathogenic fungi, are being developed promisingly in insect control. This work aimed to evaluate the pathogenicity of fungi Beauveria bassiana (Bals.) Vuill, Metarhizium anisopliae var. anisopliae (Metsch.) in workers from Acromyrmex heyeri (Forel, 1899). In a bioassay carried out in the laboratory, it was found that the concentrations were effective in the control of leaf-cutting ants. The experimental design used was completely randomized, with five replications. The material was collected on the Campus of the Federal University of Santa Maria (UFSM) in a grassland, the individuals were separated into five groups and sprayed in a suspension solution of 1.0 x 107, 1.0 x 108, 1, 0 x 109 mL-1 conidia from each isolate. The control treatment received 5mL of the 0.1% Tween® 80 solution. Each group of ants was kept at a temperature of 27 ± 2 ° C. Ant mortality was obtained on the third day of the experiment. The two fungi were efficient in controlling ants, but only the B. bassiana fungus in the 1.0 x 108 and 1.0 x 109 spore concentrations stood out from the other treatments, causing higher mortality rates. The fungi B. bassiana and M. anisopliae have the potential to control A. heyri.